Comparative study of 2 software programs for predicting profile changes in Class III patients having double-jaw orthognathic surgery - Magro Filho, Osvaldo [UNESP]; Magro-Ernica, Natasha; Queiroz, Thallita Pereira; Aranega, Alessandra Marcondes [UNESP]; Garcia, Idelmo Rangel [UNESP] (Mosby-elsevier, 2010)
Introduction: Computer software can be used to predict orthognathic surgery outcomes. The aim of this study was to subjectively compare the soft-tissue surgical simulations of 2 software programs. Methods: Standard profile pictures were taken of 10 patients with a Class III malocclusion and a concave facial profile who were scheduled for double-jaw orthognathic surgery. The patients had horizontal maxillary deficiency or horizontal mandibular excess. Two software programs (Dentofacial Planner Plus [Dentofacial Software, Toronto, Ontario, Canada] and Dolphin Imaging [version 9.0, Dolphin Imaging Software, Canoga Park, Calif]) were used to predict the postsurgical profiles. The predictive images were compared with the actual final photographs. One hundred one orthodontists, oral-maxillofacial surgeons, and general dentists evaluated the images and were asked whether they would use either software program to plan treatment for, or to educate, their patients. Results: Statistical analyses showed differences between the groups when each point was judged. Dolphin Imaging software had better prediction of nasal tip, chin, and submandibular area. Dentofacial Planner Plus software was better in predicting nasolabial angle, and upper and lower lips. The total profile comparison showed no statistical difference between the softwares. Conclusions: The 2 types of software are similar for obtaining 2-dimensional predictive profile images of patients with Class III malocclusion treated with orthognathic surgery. (Am J Orthod Dentofacial Orthop 2010; 137: 452.e1-452.e5)